Antiobesity and lipid-lowering effects of Bifidobacterium spp. in high fat diet-induced obese rats - An, Hyang Mi (BioMed Central, 2011)
BACKGROUND: Recent studies have reported the preventive effects of probiotics on obesity. Among commensal bacteria, bifidobacteria is one of the most numerous probiotics in the mammalian gut and are a type of lactic acid bacteria. The aim of this study was to assess the antiobesity and lipid-lowering effects of Bifidobacterium spp. isolated from healthy Korean on high fat diet-induced obese rats. METHODS: Thirty-six male Sprague-Dawley rats were divided into three groups as follows: (1) SD group, fed standard diet; (2) HFD group, fed high fat diet; and (3) HFD-LAB group, fed high fat diet supplemented with LAB supplement (B. pseudocatenulatum SPM 1204, B. longum SPM 1205, and B. longum SPM 1207; 10(8 )~ 10(9 )CFU). After 7 weeks, the body, organ, and fat weights, food intake, blood serum levels, fecal LAB counts, and harmful enzyme activities were measured. RESULTS: Administration of LAB reduced body and fat weights, blood serum levels (TC, HDL-C, LDL-C, triglyceride, glucose, leptin, AST, ALT, and lipase levels), and harmful enzyme activities (β-glucosidase, β-glucuronidase, and tryptophanase), and significantly increased fecal LAB counts. CONCLUSION: These data suggest that Bifidobacterium spp. used in this study may have beneficial antiobesity effects.